Steering Endogenous Butyrate Production in the Intestinal Tract of Broilers as a Tool to Improve Gut Health - Onrust, Lonneke; Ducatelle, Richard; Van Driessche, Karolien; De Maesschalck, Celine; Vermeulen, Karen; Haesebrouck, Freddy; Eeckhaut, Venessa; Van Immerseel, Filip (Frontiers in Veterinary Science, 2015)
The ban on antimicrobial growth promoters and efforts to reduce therapeutic antibiotic usage has led to major problems of gastrointestinal dysbiosis in livestock production in Europe. Control of dysbiosis without the use of antibiotics requires a thorough understanding of the interaction between the microbiota and the host mucosa. The gut microbiota of the healthy chicken is highly diverse, producing various metabolic end products, including gases and fermentation acids. The distal gut knows an abundance of bacteria from within the Firmicutes Clostridium clusters IV and XIVa that produce butyric acid, which is one of the metabolites that is sensed by the host as a signal. The host responds by strengthening the epithelial barrier, reducing inflammation, and increasing the production of mucins and antimicrobial peptides. Stimulating the colonization and growth of butyrate producing bacteria thus may help optimizing gut health. Various strategies are available to stimulate butyrate production in the distal gut. These include delivery of prebiotic substrates that are broken down by bacteria into smaller molecules which are then used by butyrate producers, a concept called cross-feeding. Xylo-oligosaccharides (XOS) are such compounds as they can be converted to lactate which is further metabolized to butyrate. Probiotic lactic acid producers can be supplied to support the cross-feeding reactions. Direct feeding of butyrate producing Clostridium cluster IV and XIVa strains are a future tool provided that large scale production of strictly anaerobic bacteria can be optimized. Current results of strategies that promote butyrate production in the gut are promising. Nevertheless, our current understanding of the intestinal ecosystem is still insufficient, and further research efforts are needed to fully exploit the capacity of these strategies.